Indianness in Malaysia: Between Racialized Representations and the Cultural Politics of Popular Music - Mandal, Sumit K. (Kasarinlan: Philippine Journal of Third World Studies; Vol 22 No 2 (2007): Culture and Identity, 2008)
Perspectives based on race or essentialized notions of ethnicity have had remarkable resilience in the study of Malaysia despite their rather dubious use. Undoubtedly, a racialized polity has arisen as a result of the preferential treatment given to those classified under the nativistic politico-legal category Bumiputera (indigene). Boundaries are nevertheless more permeable than often admitted by politicians. By turning to the case of Indian Malaysians, I explore how the dominance of racialized perspectives in public discourse in Malaysia renders inconsequential if not invisible the rich and complex interaction between different ethnic groups. I show how dominant representations of Indian Malaysians obscure the significant and distinctive efforts of popular musicians. The state, opposition politicians, and nongovernment organizations tend to represent Indians as a singularly disempowered minority. This concurrence of views affirms the racialized political and social order and diminishes the potential alternatives, if not the challenges, posed by transethnic, hybrid, and other forms of cultural politics. The complexity of Indianness and, indeed, ofMalaysian society resists racialized perspectives. This becomes especially clear when we turn to the cultural politics of popular music in Peninsular Malaysia. Young musicians produce work in the genres of rock, hip-hop, reggae, and so forth in Tamil—the most commonly spoken language of Indian origin—as well as in other Malaysian languages. An admixture of rebellion and commercial drive colors their efforts as they capitalize on the enabling aspects of globalization while trying to curb its damaging consequences. As a result of their exposure to—if not familiarity with—different cultures and languages, and through contact, exchange and partnership with musicians of other ethnic backgrounds, Indian Malaysians have forged a distinct musical identity.
Keywords: Ethnicity, race, identity, cultural politics, popular music, Indianness, Malaysia